Usage of Ray Tracing Transfer Matrix to Mitigate the Stray Light for ITER Spectroscopy. Issue 9 (4th May 2016) - Kajita, S.; Veshchev, E.; Barnsley, R.; Walsh, M.
Abstract: Stray light formed by the reflection of photons on inner wall from a bright divertor region can be a serious issue in spectroscopic measurement systems in ITER. In this study, we propose a method to mitigate the influence of stray light using a ray tracing analysis. Usually, a ray tracing simulation requires a time consuming runs. We constructed transfer matrices based on the ray tracing simulation results and used them to demonstrate the influence of stray light. It is shown that the transfer matrix can be used to reconstruct the emission profile by considering the influence of the stray light without any additional ray tracing runs. Mitigation of the stray light in ITER divertor impurity monitor was demonstrated, and a method of prediction of the stray light level for the scrape off layer spectroscopy from divertor region was proposed. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)